Assessing Teachers’ Readiness and Infrastructure Needs for Digital Classroom Development through a Service-Learning Approach - Al Husna, Hafizhah; Nurlaili, Nurlaili (PT Agung Media Publisher, 2025)
Digital transformation in education requires a deep understanding of teacher readiness, infrastructure availability, and pedagogical needs. This study employs a service-learning approach to conduct a needs analysis for the development of a digital classroom at MTs Rambatan. The study involved 15 teachers who completed a 13-item online questionnaire distributed via Google Forms. Data were analyzed descriptively using frequency distributions to identify teachers’ perceptions, readiness, and infrastructural conditions related to digital classroom implementation. Findings indicate strong recognition of the need for innovation, with 100% of teachers agreeing that innovation is necessary and 53% perceiving the current learning environment as inadequate. Teachers showed high optimism about digital classrooms, with 100% agreeing that they can improve learning interest and outcomes. Readiness levels were equally promising, as 60% reported being ready and 40% very ready to adopt digital classrooms; 100% also expressed the need for further training. However, ICT infrastructure remains insufficient: 40% rated device availability as inadequate, and only 7% considered it very adequate. Teachers at MTs Rambatan exhibit strong motivation, readiness, and awareness regarding digital classroom development. However, inadequate ICT infrastructure poses a major challenge that requires institutional support and strategic investment. Future research should expand the scope of participants and examine the effectiveness of digital classroom implementation through longitudinal and experimental methods.